Geometry, fractal dimension and settling velocity of flocs during flooding conditions in the Rhône ROFI. (5th April 2019) - Many, G.; Durrieu de Madron, X.; Verney, R.; Bourrin, F.; Renosh, P.R.; Jourdin, F.; Gangloff, A.
Abstract: Regions Of Freshwater Influence (ROFI) are of particular interest in a source-to-sink approach in terms of sediment advection, settling, and deposition in the coastal zone. An experiment was carried out in the ROFI of the Rhône River in February 2016 to describe the properties of suspended particulate matter (SPM) during a flood event. A digital holographic camera (LISST-HOLO, 20–2000 μm) was used to estimate the variability of fine sediment floc properties (size, nature and shape) formed in the Rhône mouth. An automatic image toolbox was developed to classify the different constituents of the SPM (as diatoms, bubbles and flocs) and to describe the diversity of floc shapes existing in the material in suspension. We estimated the fractal dimension (DF3D ), the aspect ratio (AR) and the settling velocity of flocs (Ws ). The estimated DF3D ranged between 2.0 and 2.5 highlights the complexity of floc shape, which was used as a proxy of the flocculation mechanism functioning in the Rhône mouth. Additionally, we performed a sensitivity analysis on the estimate of Ws using different shape-related coefficients (α/β) and primary particle size (dP ). The results highlighted the impact of the flocculation of fine sediments on the increase of Ws from 0.01 to 3 mm s −1 when floc sizes increase from 30 to 500 μm. Ws showed a decrease of 41% considering the sphericity of flocs that emphasized the need to consider the floc shape to properly estimate their settling velocity. We showed that an increase of dP from 1 to 12 μm induces a fivefold increase of Ws that showed the need for an adequate system to properly estimate the size of primary particles. These results emphasized the need to take into account such variability in future model of floc dynamics in ROFI to properly estimate plume sinking rate and SPM dynamics. Highlights: Description of fine sediment floc properties in the Rhône River ROFI. Evidence of the diversity of floc shapes existing in the material in suspension. Flocculation increases of two orders the settling velocity of fine sediments. Evidence of the decrease of floc settling velocities considering floc shapes.